Alocação de endereços IPv6 em redes sem fio multi-hop de baixa potência - Bruna Soares Peres (2015)
Many low-power wireless networks are based on mechanisms that maintain cycle-free topologies to support data-collection applications. The network is typically optimized for bottom-up data traffic, and eventual packets that need to be sent in a different direction must follow longer paths and are frequently dropped due to lack of memory for the necessary routing tables, which can require O(n) memory space, where n is the size of the subtree rooted at each routing node. In this work we propose a Multihop Host Configuration strategy that explores cycle-free network structures in low-power wireless networks to generate and assign IPv6 addresses to nodes. The objective is to enable efficient and robust top-down routing with low memory footprint. MHCL generates and assigns IPv6 addresses which reflect the topology of the underlying wireless network. As a result, routing tables for top-down data traffic are of size O(k), where k is the number of children of each routing node. We implemented our strategy as a subroutine of RPL protocol in Contiki OS. We performed experiments to show that our strategy is efficient in time and number of messages, and is robust to network dynamics, caused by changes in preferred parents and failures in network links and nodes.